العلاقة البينية للإحساس والإدراك في التصميم المعماري - قصاب, أحمد; الحلبية, صباح (Latakia University Journal -Engineering Sciences Series, 2019)
نظراً لأهمية إحساس الإنسان بما يحيط حوله من أشخاص أو أشياء أو أوساط وفراغات والذي يجعل لكل شيء في حياته معنى مختلفاً وذو قيمة مادية أو عاطفية أو كليهما، كان لابد من دراسة معنى ومفهوم الإحساس وتفسير آلية الوصول إليه، تحويل الأشياء المحسوسة في المحيط إلى مدركات ذات قيمة عقلية ورقمية، وأيضا في محاولة لتفسير المدركات ذات القيم العقلية والعلمية والرقمية عبر وسائط تحليلية فكرية تطبيقية ميدانية للوصول إلى أحاسيس وشعور بالمبنى . وهذا ما قاد البحث إلى ضرورة معرفة الفرق بين كل من الإحساس والإدراك من جهة ،و البحث في آلية التحليل الوسيطة للانتقال البيني بالاتجاهين المتعاكسين بين الإحساس والإدراك . ولأن العمارة أحد أهم الفراغات التي تشغل فكر وعاطفة المستخدمين ماديا و عاطفيا، تم العمل على دراسة وتحليل إقحام الإحساس العاطفي للمستخدمين في عملية التصميم وتفسير الإحساس وصولا إلى إدراك عقلي وأهمية التصميم وفق عملية إدراك عقلية للوصول إلى إحساس عاطفي ايجابي يرضي المستخدمين . Because of the importance of the human sense of the surrounding people, objects or circles and spaces, which makes everything in his life a different meaning and material or emotional value or both, it was necessary to study the meaning and concept of sense and interpretation of the mechanism of access to the conversion of tangible things in the ocean to perceptions of the same Mental and digital values, as well as in an attempt to interpret perceptions of mental, scientific and digital values through analytical, applied field-based analytical media to reach the senses and feelings of the building. This led the research to the need to know the difference between the sense and perception on the one hand, and research in the mechanism of the analysis of the intermediate of the inter-transfer between the two directions between the sensation and perception. Because architecture is one of the most important spaces that occupy the mind and passion of the users materially and emotionally, the study and analysis of the emotional sensation of users in the process of design and interpretation of the sense to reach the mental perception and the importance of design in accordance with the process of mental perception to reach a positive emotional feeling to the satisfaction of users.